2009
DOI: 10.1161/atvbaha.109.185223
|View full text |Cite
|
Sign up to set email alerts
|

Sphingomyelin Synthase 2 Is One of the Determinants for Plasma and Liver Sphingomyelin Levels in Mice

Abstract: Background-It has been proposed that plasma sphingomyelin (SM) plays a very important role in plasma lipoprotein metabolism and atherosclerosis. Sphingomyelin synthase (SMS) is the last enzyme for SM de novo biosynthesis. Two SMS genes, SMS1 and SMS2, have been cloned and characterized. Methods and Results-To evaluate the in vivo role of SMS2 in SM metabolism, we prepared SMS2 knockout (KO) and SMS2 liver-specific transgenic (LTg) mice and studied their plasma SM and lipoprotein metabolism. On a chow diet, SMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 40 publications
7
69
3
Order By: Relevance
“…Critical roles for lipid microdomains in fatty acid uptake and maturation of lipid droplets have been reported (28,34). In addition, SMS2 deficiency reportedly reduced sensi-tivity to lysenin-mediated cytolysis, indicating that SMS2 alters the lipid microdomain (35). Methyl-␤-cyclodextrin (M␤CD) is known to reduce cholesterol levels, disrupt lipid microdomains, and induce cell death (36).…”
Section: Sms2 Is Involved In Large Lipid Droplet Formation In Liver-mentioning
confidence: 99%
“…Critical roles for lipid microdomains in fatty acid uptake and maturation of lipid droplets have been reported (28,34). In addition, SMS2 deficiency reportedly reduced sensi-tivity to lysenin-mediated cytolysis, indicating that SMS2 alters the lipid microdomain (35). Methyl-␤-cyclodextrin (M␤CD) is known to reduce cholesterol levels, disrupt lipid microdomains, and induce cell death (36).…”
Section: Sms2 Is Involved In Large Lipid Droplet Formation In Liver-mentioning
confidence: 99%
“…Ceramides serve as "metabolic hub" and cells are equipped with a multitude of enzymes to modulate their levels. This may explain why genetic ablation of SMS1 and SMS2 in mice causes only a modest increase in tissue ceramide levels [ ( 13,15,27 ), and this study], even though these enzymes normally consume the bulk of newly synthesized ceramides ( 10 ). As tissues of SMSrD348E mutant mice did not contain any signifi cantly elevated levels of sphingoid bases, hexosylceramides, or SM, it is unclear how embryonic cells with disrupted SMSr catalytic activity were able to overcome a deregulation of ER ceramides associated with a disruption in SMSr catalytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we generated mouse lines lacking SMSr catalytic activity and crossbred these with SMS2-null mice ( 27 ) of wild-type heterozygous (+/SMSrD348E or +/SMSrdelEx6) and homozygous (SMSrD348E or SMSrdelEx6) mice. For the SMSrD348E mice, DNA was digested with Bcl I and a 5 ′ external probe binding downstream of exon 1 and upstream of the 5 ′ HR was used.…”
Section: Generation Of the Conditional Smsrdelex6 Vectormentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, it was indicated that hepatic SMS activity increased following LPS treatment, and this implied that the cause of the increase in SMS activity and SM content was the overexpression of SMS2, but not of SMS1. SMS2 is the principal enzyme that takes charge of the biosynthesis of SM in the liver (26).…”
Section: Discussionmentioning
confidence: 99%